Organizational Support for Entrepreneurial Orientation: The Perception of Professionals from Early Childhood Education Centers in Brazil - Luciana dos Santos Vieira; Daniela Andrade Meirelles; Magnus Emmendoerfer (Springer, 2023)
Entrepreneurial Orientation (EO) has become increasingly prominent in the public sector and in educational organizations. A policy for educational management based on EO has dimensions related to innovation, proactiveness, and risk-taking, which are preceded by organizational characteristics such as management support, discretion/autonomy, rewards/recognition, organizational boundaries, and time availability. The objective of this study is to analyze the organizational characteristics that influence EO in Municipal Centers for Early Childhood Education (Centros Municipais de Educação Infantil - CEMEIs) in Brazil. The study was conducted in a town in the state of Minas Gerais and involved 15 CEMEIs, applying questionnaires to education professionals as coordinators, monitors, and teachers, whose data were processed using descriptive statistics and a structural equation model. The results present a construct for validating organizational characteristics that can influence EO in public early childhood education organizations. However, autonomy and management support were the determinants of EO in the organizations studied. Finally, there are implications and considerations for policies and strategies in public educational organizations, indicating EO as a way to deal with contingencies, resource scarcity, the stimulation of (intra)entrepreneurial culture and even potential early childhood education for entrepreneurship.